Petrogenesis of late carboniferous adakitic dikes and granodiorites in the Chinese Altai, NW China: Implications for lower crustal melting and slab roll-back - Shuaiyu Guo; Jiyuan Yin; Mike Fowler; Andrew C. Kerr; Yunchuan Zeng; Zaili Tao; Fan Yang; Jianjun Zhang; Tao Wang; Wenjiao Xiao (Lithos, 2026)

Closure of the Strait of Hormuz may trigger a bioinvasion super-spreader event - Mario N. Tamburri; James T. Carlton; April M. H. Blakeslee; Alejandro Bortolus; João Canning-Clode; Susana Carvalho; Andrew L. Chang; Ian C. Davidson; Sarah C. Donelan; Lisa A. Drake; Amy E. Fowler; Amy L. Freestone; et al. (Biological Invasions, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Associations Between Diet Quality and Psychosocial and Environmental Factors in Rural Adults - Rebecca A. Seguin-Fowler; Karla L. Hanson; Galen D. Eldridge; Grace A. Marshall; Meredith L. Graham; Miriam E. Nelson; Deyaun L. Villarreal; Johanna Y. Andrews Trevino; Jay E. Maddock (Journal of Nutrition Education and Behavior, 2026)

Rapid recycling of sediment-derived granites in accretionary orogens: Implications from the Alataw Mountains, NW China - Jiyuan Yin; He Huang; Ilya Bindeman; Chiara Maria Petrone; Mike Fowler; Andrew C. Kerr; Zaili Tao; Tao Wang; Min Sun; Guochun Zhao; Wenjiao Xiao (Chemical Geology, 2026)

Stress testing water allocations across large river basins - Avril Horne; Andrew John; Keirnan Fowler; Ziqi Zhang; Rory Nathan (Climatic Change, 2025)
Water scarcity is a growing global challenge, with climate change exacerbating pressures on water security and allocation. Increasingly approaches such as stress testing, scenario neutral methods and decisions scaling are being suggested to identifying system vulnerabilities by systematically varying climate inputs to better understand the system response and thresholds of impacts. However, applying such approaches to large river basins presents technical challenges in making the computational process tractable. This study develops a novel, rapid-assessment method to stress test water allocations in large, complex river basins, applying it to the Southern Connected Murray-Darling Basin in Australia. The method combines stochastic climate projections, rainfall–runoff modelling, and statistical allocation modelling to evaluate how changes in precipitation, temperature, and runoff affect water availability and allocations. We assess the implications of spatial differences in climate, runoff response, and allocation policy across major rivers in the basin. Our results highlight substantial spatial variation in climate sensitivity and demonstrate that water allocation policy plays a critical role in mediating climate impacts. Among the three factors examined, the structure of the water allocation policy had the greatest influence on system robustness (i.e. is the inherent capacity of a system to withstand a range of conditions). This is particularly evident in the Murray reservoirs, where two different allocation systems produce markedly different outcomes under climate change. The approach offers a scalable framework for evaluating climate risks to water resources in regulated river systems worldwide, and an additional tool for rapid assessment of water allocation impacts in large river basins.

Caribbean Creep meets Chesapeake Creep: marine bioinvasions and community shifts along the Mid-Atlantic Coast, USA - Amy E. Fowler; April M. H. Blakeslee; Andrew Davinack; Robert Aguilar; Miranda Andersen; Clara Benadon; Henry H. C. Choong; Lindsay Green-Gavrielidis; Sarah R. Greenberg; El Hartshorn; Niels-Viggo Hobbs; Sara Labbe; et al. (Biological Invasions, 2025)
The Mid-Atlantic waters of North America are warming faster than > 90% of other global oceans, leading to significant increases in bottom water temperatures and influencing shifts in marine community structure. Given this modern-day scenario of significant community shifts over space and time, baseline surveys of species diversity are increasingly valuable. Therefore, we performed the first-ever marine bioinvasions Rapid Assessment Survey (RAS) along the Mid-Atlantic waters of the United States in June 2023, focused on marina floating pontoons in Virginia, Maryland, Delaware, and New Jersey. We recorded 29 non-indigenous, 16 cryptogenic, and 10 species that have expanded their ranges in the mid-Atlantic. Seven of these 10 species have expanded northwards from southern locations in the Caribbean (“Caribbean Creep”) or the western Atlantic (“Chesapeake Creep”), and three have expanded southwards. Five non-indigenous species (NIS) were found at more than 60% of the 10 sampled sites: the bryozoans Bugula neritina , Schizoporella pungens , Tricellaria inopinata, macroalgae Codium fragile subsp. fragile , and the sea anemone Aiptasiogeton eruptaurantia . We did not document any new nonindigenous species not already recorded on the Western Atlantic coast. All 10 communities were distinctly different, and species dominance varied by latitude and by site. This first-ever RAS of the Mid-Atlantic waters of the United States provides critical insight into how marine communities have been and are changing as a result of colonization by NIS, including those that have expanded their ranges as a result of human-induced climate change.

Cretaceous to Cenozoic Magmatic and Crustal Evolution of the Pamir-West Kunlun Orogenic Belt - Fan Yang; Jiyuan Yin; Mike Fowler; Andrew C. Kerr; Zaili Tao (Journal of Earth Science, 2025)

High-resolution climate models improve simulation of monsoon rainfall changes in the Ganga–Brahmaputra-Meghna basin - Haider Ali; Hayley J. Fowler; Andrew G. Turner (Climate Dynamics, 2025)
This study investigates the impact of model resolution on simulating South Asian monsoon rainfall, focusing on the Ganges–Brahmaputra-Meghna (GBM) basin. By comparing high- and low-resolution versions of four CMIP6 HighResMIP model families against reference datasets (MSWEP and ERA5), we emphasize the advantages of high-resolution models in accurately simulating key monsoon characteristics, including annual rainfall, timing, intensity, and duration. Our results show that the high-resolution models align more closely with observed data, outperforming their low-resolution counterparts. Between 1979 and 2014, the high-resolution model ensemble (HR-models) captures key shifts in monsoon timing, such as delayed onset and withdrawal, leading to a slight increase in monsoon duration. In contrast, the low-resolution ensemble (LR-models) showed more pronounced delays in onset. The observational datasets, MSWEP and ERA5, indicate earlier (7 ± 3 days) and later (3 ± 1.2 days) onsets, respectively, with both showing delays in withdrawal, indicating extended monsoon duration. Notably, the increase in monsoon duration is more pronounced in MSWEP observations than in the model simulations, particularly for LR-models. Regarding rainfall trends, the HR-models more accurately reflect observed changes in both total rainfall and extreme rainfall from 1979–2014 compared to LR-models. Future projections (2015–2050) indicate further delays in monsoon onset, with HR-models projecting larger increases in total rainfall and extreme events (up to 4.5%/decade for the 95th percentile of rainfall) compared to LR-models, which show smaller increases and higher variability in total and extreme rainfall. These findings highlight the critical role of model resolution in improving the accuracy of monsoon simulations, with HR models offering more reliable simulations of historical monsoon behaviour and therefore likely more robust projections of future monsoon behavior. These are essential for informed water management and agricultural decision-making over the complex topography of the GBM basin.

A climatology of local hourly wet spells across the tropics - Vincent Moron; Erwan Cornillault; Haider Ali; Hayley J. Fowler; Andrew W. Robertson (Climate Dynamics, 2025)

Household Food Sourcing Patterns and Their Associations With Food Insecurity in Appalachian Ohio - Kyle R. Busse; Kathryn I. Poppe; Qiang Wu; Stephanie B. Jilcott Pitts; Lindsey Haynes-Maslow; Alice S. Ammerman; Kathleen Krzyzanowski Guerra; Zoë Plakias; Andrew S. Hanks; Katharine Garrity; Rachel Gillespie; Bailey Houghtaling; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Self-swabbing versus assisted swabbing for viral detection by qRT-PCR: the experience from SARS-CoV-2 based on a meta-analysis of six prospectively designed evaluations conducted in a UK setting - Tom Fowler; David Chapman; Matthias E. Futschik; Sarah A. Tunkel; Edward Blandford; Elena Turek; Olumide Kolade; Sergio Souza da Cunha; Andrew Dodgson; Paul Klapper; Malur Sudhanva; Lindsey Davies; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose In April 2020, the UK Government implemented NHS Test and Trace to provide SARS-CoV-2 quantitative reverse transcription polymerase chain reaction (qRT-PCR) testing for the public, with nose-and-throat swabbing for samples performed by trained staff. Self-swabbing (SS) would allow rapid scale-up of testing capacity and access. Six studies were undertaken to determine whether SS was as effective for detecting SARS-CoV-2 as swabbing performed by trained staff. Methods Six prospective studies were conducted between April–October 2020, using six swab/media combinations. Differences between assisted swabbing (AS) and SS were evaluated for concordance, positivity, sensitivity, cycle threshold (Ct) values and void rates. Statistical analysis was performed using 95% confidence intervals (CIs), paired t-tests and model-based methods. Results Overall, 3,253 individuals were recruited (median age 37 years, 49% female), with 2,933 having valid paired qRT-PCR results. Pooled concordance rate was 98% (95% CI: 96%, 99%). Positivity rate differences for SS (8.1%) and AS (8.4%) and differences in pooled sensitivities between SS (86%; 95% CI: 78%, 92%) and AS (91%; 95% CI: 78%, 96%) were nonsignificant. Both types of swabbing led to pooled void rates below 2% and strongly correlated Ct values. Age, sex and previous swabbing experience did not have a significant impact on concordance or sensitivity. Conclusion The UK adopted a policy to promote self-testing for SARS-CoV-2 based on data demonstrating equivalence of SS versus AS. Positive outcomes with SS are likely generalisable to testing for other respiratory pathogens, and we consider self-sampling and self-testing essential for future pandemic preparedness.

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Passive biomonitoring for per- and polyfluoroalkyl substances using invasive clams, C. fluminea - Lauren A. Koban; Tabitha King; Thomas B. Huff; Kirin E. Furst; T. Reid Nelson; Andrew R. Pfluger; Mrudula Meghana Kuppa; Amy E. Fowler (Journal of Hazardous Materials, 2024)

Utilization of an Advanced Sensor network to determine fuel heating value and Real-Time net unit heat rate during transient operation - Keane Stewart; Connor Moran; Kensley Fowler; David McFarland; Kody Powell; Jacob Tuttle; Andrew Fry (Fuel, 2024)

Maturation from oceanic arcs to continental crust: Insights from Paleozoic magmatism in West Junggar, NW China - Jiyuan Yin; Wenjiao Xiao; Tao Wang; Mike Fowler; Andrew C. Kerr; Min Sun; Rob Strachan; He Huang; Ji'en Zhang; Wen Chen; Zaili Tao (Earth-Science Reviews, 2024)

The role of the community café in addressing food security: Perceptions of managers and directors - Andrew McNeely; Lori Borchers; Jacob Szeszulski; Heather A. Eicher-Miller; Rebecca A. Seguin-Fowler; Alexandra MacMillan Uribe (Appetite, 2024)

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

To what extent can decommissioning options for marine artificial structures move us toward environmental targets? - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Nicola Beaumont; Silvana Birchenough; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Attribution of the heavy rainfall events leading to severe flooding in Western Europe during July 2021 - Jordis S. Tradowsky; Sjoukje Y. Philip; Frank Kreienkamp; Sarah F. Kew; Philip Lorenz; Julie Arrighi; Thomas Bettmann; Steven Caluwaerts; Steven C. Chan; Lesley De Cruz; Hylke de Vries; Norbert Demuth; et al. (Climatic Change, 2023)
In July 2021 extreme rainfall across Western Europe caused severe flooding and substantial impacts, including over 200 fatalities and extensive infrastructure damage within Germany and the Benelux countries. After the event, a hydrological assessment and a probabilistic event attribution analysis of rainfall data were initiated and complemented by discussing the vulnerability and exposure context. The global mean surface temperature (GMST) served as a covariate in a generalised extreme value distribution fitted to observational and model data, exploiting the dependence on GMST to estimate how anthropogenic climate change affects the likelihood and severity of extreme events. Rainfall accumulations in Ahr/Erft and the Belgian Meuse catchment vastly exceeded previous observed records. In regions of that limited size the robust estimation of return values and the detection and attribution of rainfall trends are challenging. However, for the larger Western European region it was found that, under current climate conditions, on average one rainfall event of this magnitude can be expected every 400 years at any given location. Consequently, within the entire region, events of similar magnitude are expected to occur more frequently than once in 400 years. Anthropogenic climate change has already increased the intensity of the maximum 1-day rainfall event in the summer season by 3–19 %. The likelihood of such an event to occur today compared to a 1.2 $$^{° }$$ ∘ C cooler climate has increased by a factor of 1.2–9. Models indicate that intensity and frequency of such events will further increase with future global warming. While attribution of small-scale events remains challenging, this study shows that there is a robust increase in the likelihood and severity of rainfall events such as the ones causing extreme impacts in July 2021 when considering a larger region.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

The time of emergence of climate-induced hydrologic change in Australian rivers - Andrew John; Rory Nathan; Avril Horne; Keirnan Fowler; Michael Stewardson; Murray Peel; J. Angus Webb (Journal of Hydrology, 2023)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Assessment of Australian Sea Lion Bycatch Mortality in a Gillnet Fishery, and Implementation and Evaluation of an Effective Mitigation Strategy - Simon D. Goldsworthy; Brad Page; Derek J. Hamer; Andrew D. Lowther; Peter D. Shaughnessy; Mark A. Hindell; Paul Burch; Daniel P. Costa; Shannon L. Fowler; Kristian Peters; Rebecca R. McIntosh; Frederic Bailleul; et al. (Frontiers in Marine Science, 2022)
Globally, the bycatch of marine mammals in fisheries represents the greatest source of human-caused mortality that threatens the sustainability of many populations and species. The Australian sea lion ( Neophoca cinerea ) is an endangered species, whose populations off South Australia (SA) have been subject to bycatch in a demersal gillnet fishery targeting sharks since the 1960s. A comprehensive assessment was undertaken of sea lion bycatch mortality that combined independent fishery observer data with species distribution models (underpinned by satellite tracking, abundance data and population modeling) to model the relationship between at-sea foraging effort and bycatch rate. Combined with the distribution of fishing effort, these models enabled the overall level of bycatch mortality to be estimated by age, sex and subpopulation, facilitating population viability analyses that indicated most subpopulations were declining, and subject to unsustainable levels of bycatch mortality. To reduce this mortality, the Australian Fisheries Management Authority implemented an Australian Sea Lion Management Strategy that included an independent observer program (ultimately 100% electronic monitoring of gillnet fishing off SA), permanent spatial gillnet closures around all sea lion breeding sites, bycatch mortality limits that triggered temporal (18 months) spatial closures when zone-specific bycatch trigger limits were reached, and incentives for gillnet fishers to switch to an alternate fishing method (longlines). The Strategy had immediate impacts on the fishery: it resulted in significant reductions in gillnet fishing effort and on the reported bycatch of sea lions. In the next decade, there was an estimated 98% reduction in sea lion bycatch mortality from gillnet interactions and an apparent stabilization of the decline in sea lion pup abundances at some impacted breeding sites. There was an almost complete transition in the fishery from gillnets to longlines, and fishing catches returned to pre-management levels. The successful implementation of management measures to mitigate sea lion bycatch mortality in the gillnet fishery off SA was rapid, science informed, adaptive, comprehensive, and backed by strong compliance and monitoring of the fishery. It provides an important case study which demonstrates how management measures can be effectively applied to mitigate bycatch mortality of marine mammals and other marine protected species.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Growth impacts in a changing ocean: insights from two coral reef fishes in an extreme environment - Daniele D’Agostino; John A. Burt; Veronica Santinelli; Grace O. Vaughan; Ashley M. Fowler; Tom Reader; Brett M. Taylor; Andrew S. Hoey; Geórgenes H. Cavalcante; Andrew G. Bauman; David A. Feary (Coral Reefs, 2021)
Determining the life-history consequences for fishes living in extreme and variable environments will be vital in predicting the likely impacts of ongoing climate change on reef fish demography. Here, we compare size-at-age and maximum body size of two common reef fish species ( Lutjanus ehrenbergii and Pomacanthus maculosus ) between the environmentally extreme Arabian/Persian Gulf (‘Arabian Gulf’) and adjacent comparably benign Oman Sea. Additionally, we use otolith increment width profiles to investigate the influence of temperature, salinity and productivity on the individual growth rates. Individuals of both species showed smaller size-at-age and lower maximum size in the Arabian Gulf compared to conspecifics in the less extreme and less variable environment of the Oman Sea, suggesting a life-history trade-off between size and metabolic demands. Salinity was the best environmental predictor of interannual growth across species and regions, with low growth corresponding to more saline conditions. However, salinity had a weaker negative effect on interannual growth of fishes in the Arabian Gulf than in the Oman Sea, indicating Arabian Gulf populations may be better able to acclimate to changing environmental conditions. Temperature had a weak positive effect on the interannual growth of fishes in the Arabian Gulf, suggesting that these populations may still be living within their thermal windows. Our results highlight the potential importance of osmoregulatory cost in impacting growth, and the need to consider the effect of multiple stressors when investigating the consequences of future climate change on fish demography.

Patients with surgically treated culture-negative native joint septic arthritis have less severe disease and better outcomes - Ziv Paz; Mary Louise Fowler; Clara Zhu; Sarah B. Lieber; Andrew Moore; Robert H. Shmerling (Infectious Diseases, 2020)

Responses of soil microbiota and nematodes to application of organic and inorganic fertilizers in grassland columns - Israel Ikoyi; Bastian Egeter; Cátia Chaves; Mohammed Ahmed; Andrew Fowler; Achim Schmalenberger (Biology and Fertility of Soils, 2020)

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Responding to Climate Change: Participatory Evaluation of Adaptation Options for Key Marine Fisheries in Australia’s South East - Emily Ogier; Sarah Jennings; Anthony Fowler; Stewart Frusher; Caleb Gardner; Paul Hamer; Alistair J. Hobday; Adrian Linanne; Stephan Mayfield; Craig Mundy; Andrew Sullivan; Geoff Tuck; et al. (Frontiers in Marine Science, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Some Old Movies Become Classics – A Case Study Determining the Scientific Value of ROV Inspection Footage on a Platform on Australia’s North West Shelf - Paul G. Thomson; Ashley M. Fowler; Andrew R. Davis; Charitha B. Pattiaratchi; David J. Booth (Frontiers in Marine Science, 2018)

Navigating the complexity of ecological stability - Ian Donohue; Helmut Hillebrand; José M. Montoya; Owen L. Petchey; Stuart L. Pimm; Mike S. Fowler; Kevin Healy; Andrew L. Jackson; Miguel Lurgi; Deirdre McClean; Nessa E. O'Connor; Eoin J. O'Gorman; et al. (Ecology Letters, 2016)
Human actions challenge nature in many ways. Ecological responses are ineluctably complex, demanding measures that describe them succinctly. Collectively, these measures encapsulate the overall ‘stability’ of the system. Many international bodies, including the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, broadly aspire to maintain or enhance ecological stability. Such bodies frequently use terms pertaining to stability that lack clear definition. Consequently, we cannot measure them and so they disconnect from a large body of theoretical and empirical understanding. We assess the scientific and policy literature and show that this disconnect is one consequence of an inconsistent and one‐dimensional approach that ecologists have taken to both disturbances and stability. This has led to confused communication of the nature of stability and the level of our insight into it. Disturbances and stability are multidimensional. Our understanding of them is not. We have a remarkably poor understanding of the impacts on stability of the characteristics that define many, perhaps all, of the most important elements of global change. We provide recommendations for theoreticians, empiricists and policymakers on how to better integrate the multidimensional nature of ecological stability into their research, policies and actions.

Characterizing Uncertainty of the Hydrologic Impacts of Climate Change - Martyn P. Clark; Robert L. Wilby; Ethan D. Gutmann; Julie A. Vano; Subhrendu Gangopadhyay; Andrew W. Wood; Hayley J. Fowler; Christel Prudhomme; Jeffrey R. Arnold; Levi D. Brekke (Current Climate Change Reports, 2016)

Development of Disposal Systems for Deactivation of Unused/Residual/Expired Medications - Anushree Herwadkar; Neha Singh; Carter Anderson; Andrew Korey; William Fowler; Ajay K. Banga (Pharmaceutical Research, 2016)

The Little Ice Age climate of New Zealand reconstructed from Southern Alps cirque glaciers: a synoptic type approach - Andrew Lorrey; Nicolas Fauchereau; Craig Stanton; Petra Chappell; Steven Phipps; Andrew Mackintosh; James Renwick; Ian Goodwin; Anthony Fowler (Climate Dynamics, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Leaf Surface Roughness Elicits Leaf Swallowing Behavior in Captive Chimpanzees (Pan troglodytes) and Bonobos (P. paniscus), but not in Gorillas (Gorilla gorilla) or Orangutans (Pongo abelii) - Claudia Menzel; Andrew Fowler; Claudio Tennie; Josep Call (International Journal of Primatology, 2013)

Identification of endangered Hawaiian ducks (Anas wyvilliana), introduced North American mallards (A. platyrhynchos) and their hybrids using multilocus genotypes - Ada C. Fowler; John M. Eadie; Andrew Engilis (Conservation Genetics, 2009)

Subsistence Technology of Nigerian Chimpanzees - Andrew Fowler; Volker Sommer (International Journal of Primatology, 2007)

Leaf-swallowing in Nigerian chimpanzees: evidence for assumed self-medication - Andrew Fowler; Yianna Koutsioni; Volker Sommer (Primates, 2007)

5-Lipoxygenase polymorphism and in-vivo response to leukotriene receptor antagonists - Stephen J. Fowler; Ian P. Hall; Andrew M. Wilson; Amanda P. Wheatley; Brian J. Lipworth (European Journal of Clinical Pharmacology, 2002)

Dopamine-transporter occupancy after intravenous doses of cocaine and methylphenidate in mice and humans - S. J. Gatley; Nora D. Volkow; Andrew N. Gifford; Joanna S. Fowler; Stephen L. Dewey; Yu-Shin Ding; Jean Logan (Psychopharmacology, 1999)